Understanding users’ willingness to travel on autonomous buses: The moderating effect of experience - Molinillo-Jiménez, Sebastián; Caballero Galeote, Lidia; Liébana Cabanillas, Francisco; Ruiz Montañez, Miguel (Elsevier, 2024)
The aim of this research is to analyse the factors that influence users' willingness to travel on an autonomous bus (AB). This analysis adopted a mixed-methods approach. The findings indicated that the main antecedents of willingness to travel on an AB are perceived behavioural control, attitude and subjective norms, while the effect of personal innovativeness was seen to be lower. Trust in the AB, and perceived safety, impacted on perceived benefits, and perceived benefits impacted on satisfaction. Seven of the eight relationships proposed in the model were moderated by participants’ experience in the AB pilot test.
Keywords: Toma de decisiones; Transporte - Innovaciones tecnológicas; Autonomous bus; Artificial intelligence; Willingness to use; Attitude; Safety; Trust